Systematic Review: The Correlation Burnout Rate in Cancer Patient Caregivers - Febrianti, Erlin; Cipta, Darien Alfa; Esperanza, Maria; Handoko, Marshell Timotius; Sembiring, Melanie Darischa; Kristianti, Naftali Intania (Faculty of Medicine, Public Health, and Nursing, 2024)
The caregiver among cancer patients often experiences hardships while providing emotional, physical, and financial support for their family members. Cancer is one of the leading causes of death. However, due to improved cancer treatment, there is a reduced mortality rate and increased survival rate among patients with cancer, resulting in an increased and prolonged burden for both patients and caregivers. The caregiver is a professional in treating patients requiring extended outpatient care, assisting patients in their daily activities, and performing medical treatment. The method we used is a systematic review of the correlation between burnout rates in cancer patients' caregivers. Was also conducted a researcher's method uses a cross-sectional/study. We used 14 articles that correlated and searched the keyword cancer, patient cancer, burnout, and caregivers. Also, the results stated that caregivers are highly related to the level of burnout; thus, research shows caregivers have low self-esteem, adverse health effects, and depression. Ultimately, there is a high correlation between burnout in caregivers and cancer patients. Caregivers play a crucial role in the management of cancer patients. Giving caregivers the social support they need, educational resources, and supporting programs may decrease burnout because they need to provide for their mental health, which correlates with low self-esteem, adverse health effects, and depression. There is great potential for improvement in the design of cancer caregiver intervention studies to plan for future implementation, so more in-depth studies on this topic are needed.